1986
DOI: 10.3758/bf03200046
|View full text |Cite
|
Sign up to set email alerts
|

US preexposures retard excitatory and facilitate inhibitory conditioning of the rabbit’s nictitating membrane response

Abstract: Two experiments were conducted to examine the effects of US preexposure on differential conditioning of the rabbit's nictitating membrane response. Both experiments consisted of three phases: a 10-day US preexposure phase, a 7-day differential conditioning phase, and a 3-day retardation of learning test for inhibition. In Experiment 1, US preexposures retarded the development of excitation to CS+ but facilitated the development of inhibition to CS-. In Experiment 2, half of the preexposed subjects received the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
5
17
1
Order By: Relevance
“…First, during the preexposure phase Group 10 X 20 showed an initial increase in daily UR amplitudes that is consistent with previous reports of increases in UR amplitude over successive preexposure sessions (Mis & Moore, 1973;1986;Suboski, DiLollo, & Gormezano, 1964). However, it should be noted that the decline in the UR amplitudes observed over the last 2 days of preexposure in Group 10 X 20 is atypical and reflects the contribution of a large decrease in UR amplitude of a single subject.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…First, during the preexposure phase Group 10 X 20 showed an initial increase in daily UR amplitudes that is consistent with previous reports of increases in UR amplitude over successive preexposure sessions (Mis & Moore, 1973;1986;Suboski, DiLollo, & Gormezano, 1964). However, it should be noted that the decline in the UR amplitudes observed over the last 2 days of preexposure in Group 10 X 20 is atypical and reflects the contribution of a large decrease in UR amplitude of a single subject.…”
Section: Discussionsupporting
confidence: 79%
“…However, it should be noted that the decline in the UR amplitudes observed over the last 2 days of preexposure in Group 10 X 20 is atypical and reflects the contribution of a large decrease in UR amplitude of a single subject. Neither our previous research (Saladin & Tait, 1986) nor our subsequent research (Saladin & Tait, 1988) has produced a subject that showed a similar pattern of UR changes. Second, the retardation of the onset of conditioning in Group IO>:20 replicated previous studies that showed that 20 paraorbital shock US preexposures in each of 10 successive sessions produced retardation of excitatory nictitating membrane (Saladin & Tait, 1986) and eyelid (Hinson, 1982) conditioning in the rabbit.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While most of the studies reported the years of cocaine use, most studies did not report the amount used nor the days used in the past month of previous cocaine exposure participants had outside of the laboratory, and this may affect the magnitude of cocaine priming effects observed in the laboratory. Paradoxically, repeated exposure to cocaine outside of the relevant laboratory context might reduce priming effects observed in the laboratory, a phenomenon referred to as the "Unconditioned Stimulus-pre-exposure effect" (Randich & LoLordo, 1979;Saladin, 1986). As specified previously, the simple visual analogue scales used to assess craving are unlikely to fully reflect the multifaceted and complex nature of craving in cocaine-addicted patients (Robbins, Ehrman, Childress, & O'Brien, 1997;Tiffany & Drobes, 1991;Tiffany, Singleton, Haertzen, & Henningfield, 1993).…”
Section: Findings)mentioning
confidence: 99%
“…This lack of sensitivity, however, is not a universal feature of conditioning in the rabbit.The acquisition of the rabbit NM response is sensitive to both the global context of a training session (Hinson, 1982;Kim, 1986;Saladin & Tait, 1986) and the local context from non-US sources (Macrae & Kehoe, 1995;Rogers & Steinmetz, 1998;Weidemann & Kehoe, 1997).More specifically, the rabbit does show single alternation in hippocampal activity even when NM response does not (Hoehler & Thompson, 1979), and the rabbit shows overt singlealternation behavior during appetitive conditioning of its jaw movement (Poulos, Sheafor, & Gormezano, 1974). Even if the NM response is unique in its insensitivity to US-related contextualcues, the extinctionand reacquisition results for it indicate that, although US-related contextual cues may have a widespread influence in other response systems, they are not essential to extinction phenomena.…”
Section: Generalization Decrement Theoriesmentioning
confidence: 99%